2022
DOI: 10.1097/xcs.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cryoablation on Pectus Excavatum Repair in Pediatric Patients

Abstract: BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) involves placement of a transthoracic, retrosternal support bar under thoracoscopic guidance. Despite its minimally invasive technical approach, postoperative pain is a significant morbidity that often results in increased length of stay. Multi-modal pain control strategies have been used in the past with limited success. Recently, the use of intraoperative intercostal nerve cryoablation (CA) has been added. In the present study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…8 Several studies based on the application of thoracoscopic cryoanalgesia in MIRPE conclude a shorter hospital stay, reduced opioid consumption, and less pain compared with conventional techniques. 3,[9][10][11][12][17][18][19][20] As already described in the literature, the effect of cryoanalgesia can vary between 6 and 48 hours after application. In 2021, we conducted a study comparing patients in whom PCr was applied on the same day of PE surgery and those in whom it was applied 48 hours before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several studies based on the application of thoracoscopic cryoanalgesia in MIRPE conclude a shorter hospital stay, reduced opioid consumption, and less pain compared with conventional techniques. 3,[9][10][11][12][17][18][19][20] As already described in the literature, the effect of cryoanalgesia can vary between 6 and 48 hours after application. In 2021, we conducted a study comparing patients in whom PCr was applied on the same day of PE surgery and those in whom it was applied 48 hours before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Because demyelination is a time-dependent process, cryoablation is often combined with another immediate-acting analgesic technique, such as LA nerve blocks 91–93 . Core neural structures (epineurium, perineurium, and endoneurium) are left intact, and over time, reinnervation of the nerve through axonal regeneration occurs 93,94 . The time required for recovery is proportional to the cryoablation exposure time, 93 and recent studies suggest that reinnervation may occur more rapidly in younger patients than in adults 95 .…”
Section: Controversiesmentioning
confidence: 99%
“…The time required for recovery is proportional to the cryoablation exposure time, 93 and recent studies suggest that reinnervation may occur more rapidly in younger patients than in adults 95 . Although this mechanism has been known for decades, cryoanalgesia probes became commercially available and approved by the FDA in 2015, sparking a relatively recent increase in use for procedures with increased intercostal mediated pain, such as thoracotomy and chest wall procedures 92,94–97 . These studies have generally shown significant decreases in-hospital length of stay and opioid consumption without affecting pain scores 92,94,95,97 .…”
Section: Controversiesmentioning
confidence: 99%
See 2 more Smart Citations